Idiopathic Renal Infarction in a Previously Healthy Active Duty Soldier. Issue 2 (1st February 2014) - Eickhoff, Christa; Mei, Jian M.; Martinez, Jorge; Little, Dustin
ABSTRACT: Renal infarction (RI) is rare, and usually occurs in patients with associated comorbidities. The majority of reported cases have presented with laboratory abnormalities, most notably leukocytosis and elevated lactate dehydrogenase (LDH). A 50-year-old active duty white male nonsmoker without medical history presented with flank pain. Urinalysis, complete blood count, LDH, and serum creatinine were normal. Contrast-enhanced computed tomography of the abdomen and pelvis showed a right-sided RI. The patient was admitted to the hospital and anticoagulated. Laboratory values remained normal, and a comprehensive workup failed to reveal an etiology for his RI. RI is rare, and affected patients often present with symptoms similar to more common conditions such as lumbago or nephrolithiasis. Elevated LDH may be a clue to the diagnosis, but unlike 92% of the reviewed cases, our patient presented with a normal value. This case suggests that clinicians should consider RI in patients with persistent symptoms for whom more common causes of flank pain have been excluded; including in nonsmoking patients without apparent risk factors for infarction who present with a normal LDH and no leukocytosis.